Collaborative game-based learning with iPads and external keyboards in a web development class - Mavri, Aekaterini; Loizides, Fernando; Souleles, Nicos (My University, 2016)
Employing the iPad’s seductive powers, to facilitate active learning through stimulating intrinsic student interest, richer interactive experiences, while enjoying easy mobility and flexibility of use in multiple teaching settings, has been a popular pedagogical practice over the past few years. Previous work investigating the use of iPads for active learning in the field of web design and development in Higher Education (HE), infers that student experience and perceived learning performance was hindered by the absence of a direct point and manipulation device (i.e. a mouse), as well as cumbersome text-input activity on the touch interface. As various peripherals - aiming to transform mobile phones and tablets into production devices - are constantly being released, this study re-examines the use of iPads in the same field, by pairing external keyboards to the devices. In doing so, it seeks to elicit results about the user experience as well as the perceived student learning process and outcomes in performing practical coding exercises. Apart from the external keyboards, two additional parameters are now present: (a) a larger class size and (b) game-played learning. Results indicate a significant perceived improvement in coding performance and clear student preference in favor of the external versus the native keyboard. Issues derived from small key sizes, non-standardized layout and unconventional key combinations intended for critical functions, were recorded. The friendly competitive-collaborative approach was found to enhance the learning process. Learners showed a strong preference towards laptops, since they support multi-tasking and direct manipulation capabilities, over the iPad’s notable qualities such as portability and convenience.
Keywords: Collaboration; Mobile-enhanced learning; Code development